The Effect of Group Supportive Psychotherapy on The Hope of Patients with Advanced Breast Cancer Receiving Radiation - กรดแก้ว ภัทรพร; บรรทุมพร นุชนาถ; สุนทรไชยา รังสิมันต์ (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this quasi-experimental study was to examine the effect of group supportive psychotherapy on the hope of patients with advanced breast cancer receiving radiation. The sample consisted of 64 female outpatients diagnosed with advanced breast cancer receiving radiation therapy in 2 specialized cancer hospitals in the health service network 4. They were aged between 30 and 60 years. The 2 hospitals were randomly assigned to either the experimental or control group, and then 32 participants were randomly selected from the experimental hospital and 32 participants from the control hospital. The experimental group received the group supportive psychotherapy for 4 weeks, 60-90 minutes per session, twice a week continuously while the participants in the control group received routine nursing care. The research instruments consisted of the following: 1) Herth Hope Index 2) personal information about the participants 3) group supportive psychotherapy. All of the instruments were validated for content validity by professionals. The reliability of the instruments with Chronbach’s alpha coefficients was .81. The data were analyzed using descriptive statistics and t-test. The findings were as follows: 1) there was a significant increase in the mean of the hope scores after participating in the group supportive psychotherapy (p<.05) and 2) there was a significant difference in the mean difference in the hope scores between the pre-post interventions for both group (p<.05).